2019
DOI: 10.1158/1541-7786.mcr-18-0670
|View full text |Cite
|
Sign up to set email alerts
|

UNC-45A Is a Novel Microtubule-Associated Protein and Regulator of Paclitaxel Sensitivity in Ovarian Cancer Cells

Abstract: UNC-45A, a highly conserved member of the UCS (UNC45A/CRO1/SHE4P) protein family of cochaperones, plays an important role in regulating cytoskeletal-associated functions in invertebrates and mammalian cells, including cytokinesis, exocytosis, cell motility, and neuronal development. Here, for the first time, UNC-45A is demonstrated to function as a mitotic spindle-associated protein that destabilizes microtubules (MT) activity. Using in vitro biophysical reconstitution and total internal reflection fluorescenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 46 publications
(72 reference statements)
7
52
0
Order By: Relevance
“…We and others have previously shown that UNC-45A is a mitotic spindle-associated protein in a number of cell types including cancer cells and fibroblasts and that it has a predominantly cytoplasmic subcellular localization 5,[14][15][16] . We and others have also previously shown that UNC-45A is overexpressed in cancer versus benign tissue and in cancer cell lines versus normal cells.…”
Section: Unc45a Is Expressed In Cytoplasm and Mitotic Spindles And Ismentioning
confidence: 92%
See 4 more Smart Citations
“…We and others have previously shown that UNC-45A is a mitotic spindle-associated protein in a number of cell types including cancer cells and fibroblasts and that it has a predominantly cytoplasmic subcellular localization 5,[14][15][16] . We and others have also previously shown that UNC-45A is overexpressed in cancer versus benign tissue and in cancer cell lines versus normal cells.…”
Section: Unc45a Is Expressed In Cytoplasm and Mitotic Spindles And Ismentioning
confidence: 92%
“…10,11 This is consistent with our recently published report suggesting that UNC-45A could be a marker of chemoresistance. 5 We had previously shown that endogenous UNC-45A binds to polymerized MTs and not to free tubulin in COV-362 ovarian cancer cells. 5 Here we used a standard cosedimentation assay, which is one of the most commonly used approaches for characterizing and quantifying the ability of a protein to bind MTs, 12 to determine whether endogenous UNC-45A cofractionates with MTs in living cells.…”
Section: Expression Levels Of Unc-45a Across Cell Types and Its Co-frmentioning
confidence: 94%
See 3 more Smart Citations